British Buddhism, secular mindfulness, and the politics of sustainability - Starkey, Caroline (Religion, 2024)
The environment for Buddhist organisations in Britain has changed since the period of their initial establishment. As a result of the rise in popularity of secular mindfulness and the spread of Buddhist teachings, Buddhist groups in Britain are forced to consider their sustainability in a crowded spiritual marketplace. This article examines the recent growth of secular mindfulness teaching by Buddhist groups in Britain, drawing on new qualitative research with British Buddhist groups and teachers. I argue that ‘secular meditation’ approaches have been variously adopted by Buddhist groups to appeal to a wider range of people, bringing in much-needed revenue for financial sustainability as well as carving out greater cultural relevance. However, the boundaries between the ‘secular’ and the ‘Buddhist’ are not always clearly demarcated. As ideas and labels they operate in symbiosis, enabling Buddhist groups to navigate multiple audiences simultaneously, sustaining and developing their position in the public sphere.